Pengaruh Suplementasi terhadap Status Gizi dan Pertumbuhan Anak dengan Picky Eating: A Systematic Review - Leona Emirda Khalidazia (Lembaga Pengembangan Kinerja Dosen, 2026)
Picky eating is a problem that can lead to inadequate nutrient intake particularly calories, protein, vitamins, and minerals which can affect childern’s nutritional status. The aim of this study was to analyze the effect of nutritional supplementation on the nutritional status and growth of children with picky eating behaviors. The method used was a systematic review conducted in accordance with the PRISMA guidelines, with preschool children aged 24-72 months who exhibited picky eating as the subjects. The study results indicate that the use of Oral Nutritional Supplements (ONS) in preschool children with selective esating behaviors improves nutritional status indicators, particularly z-scores for weight-for-age, weight-for-height percentiles, and z-score for BMI-for-age. Various studies report significant increases in weight, BMI, and height in children receiving supplements compared to the control group. Supplements also increased appetite and ensured adequate micronutrient intake. However, the impact on linear growth was inconsistent across studies, likely due to the short duration of the intervention and the fact that height growth is influenced by many factors. In conclusion, oral nutritional supplementation can significantly improve nutritional status and support the growth of children with picky eating habits, particularly in terms of weight gain and ensuring adequate nutrition.